Preoperative progressive explosive-type resistance training is feasible and effective in patients with hip osteoarthritis scheduled for total hip arthroplasty – a randomized controlled trial. Issue 1 (January 2016) - Hermann, A.; Holsgaard-Larsen, A.; Zerahn, B.; Mejdahl, S.; Overgaard, S.
Summary: Objective: To investigate the efficacy and feasibility of progressive explosive-type resistance training (RT) in patients with osteoarthritis (OA) of the hip scheduled for total hip arthroplasty (THA). Method: Randomized controlled trial (1:1) in patients diagnosed with hip OA and scheduled for THA. The intervention group (IG) performed supervised preoperative progressive explosive-type RT twice a week for 10 weeks; four exercises (hip/thigh) performed in three series each (8–12 repetition maximum). The control group (CG) received 'care as usual'. Efficacy was reported as the between-group difference in the Hip Osteoarthritis Outcome Score (HOOS) (primary endpoint; ADL function), and leg muscle power at post intervention follow-up immediate before surgery. Intention-to-treat analyses were performed in a multilevel regression model adjusting for baseline, sex, age and weight. Feasibility was reported as adherence, exercise related pain and adverse effects. Post-surgical follow up will be reported separately. ClinicalTrials.gov registration:NCT01164111 . Results: Eighty patients (age 70.4 ± 7.6 years, BMI 27.8 ± 4.6, 52 females (65%) were included. Adherence was high (93%) with acceptable exercise related pain (VAS score ≤ 5) reported in 83% of sessions and no adverse events. Changes in HOOS 'function' was 10.0 points 95%CI [4.7; 15.3] higher in IG compared to CG ( P  < 0.001). For all the remaining HOOS subscales IG scored significantly better ( P  < 0.03) and had higher leg extension muscle power ( P  < 0.0001) compared to CG. Conclusion: Progressive explosive-type RT was feasible in the included group of hip OA patients scheduled for THA and resulted in significant improvement in self-reported outcomes and increased leg muscle power.